New insights into the genetic diversity of Schistosoma mansoni and S. haematobiumin Yemen. Issue 1 (December 2015) - Sady, Hany; Al-Mekhlafi, Hesham; Webster, Bonnie; Ngui, Romano; Atroosh, Wahib; Al-Delaimy, Ahmed; Nasr, Nabil; Chua, Kek; Lim, Yvonne; Surin, Johari
Abstract Background Human schistosomiasis is a neglected tropical disease of great importance that remains highly prevalent in Yemen, especially amongst rural communities. In order to investigate the genetic diversity of humanSchistosoma species, a DNA barcoding study was conducted onS. mansoni andS. haematobium in Yemen. Methods A cross-sectional study was conducted to collect urine and faecal samples from 400 children from five provinces in Yemen. The samples were examined for the presence ofSchistosoma eggs. A partial fragment of the schistosomecox 1 mitochondrial gene was analysed from each individual sample to evaluate the genetic diversity of theS. mansoni and S.haematobium infections. The data was also analysed together with previous publishedcox 1 data forS. mansoni and S.haematobium from Africa and the Indian Ocean Islands. Results Overall, 31.8 % of participants were found to be excreting schistosome eggs in either the urine or faeces (8.0 % S. mansoni and 22.5 % S. haematobium ). Nineteen unique haplotypes ofS. mansoni were detected and split into four lineages. Furthermore, nine unique haplotypes ofS. haematobium were identified that could be split into two distinct groups. Conclusion This study provides novel and interesting insights into the population diversity and structure ofS. mansoni andS. haematobium in Yemen. The data adds to our understanding of the evolutionary history and phylogeography of these devastating parasites whilst the genetic information could support the control and monitoring of urogenital and intestinal schistosomiasis in these endemic areas.